Students’ Visualization Skills in Chemical Bonding through Three Dimension: A Study on Secondary School Chemistry Students - Aliyu, Faruku; Garba, Aliyu; Faruk, Ramatu Umar (Journal of Natural Science and Integration, 2023)
Visual cognitive representation of chemical structures and composition is achieved when proper visualization is made by chemistry students. It is in respect this that, this study measured the students’ visualization skills in chemical bonding through three dimension: a study on secondary school chemistry students. The study adopted quasi-experimental group design where both experimental (students taught using 3D visualization) and control (students taught using 2D visualization) groups participated in pre-test and post-test but only the experimental group received the intervention as 3D visualization.  The population for this research comprises all science senior secondary school one (SSS1) students under Sokoto State Ministry of Science and Technology, Sokoto State, Nigeria. A sample of 118 students purposively selected were used. The instrument used for this research was Students’ Visualization Test in Chemical Bonding (SVTCB). The measured reliability of the instruments was 0.72.  Independent sample t-test was used to analyse data collected. The findings implies that, 3D visualization enhances students’ visualization skills in the learning of chemistry abstract concept irrespective of gender. Keywords:  Visual, Cognitive, Skills, Chemical Bonding, 3D